HAKIKAT SERVICE QUALITY PADA NASABAH BANK SYARIAH MELALUI CUSTOMER SATISFACTION SEBAGAI KETAATAN HUKUM - S, Hengki Firmanda. (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
The purposes of Islamic Banking in general are as social institutions and providers of welfare effects for society. The noble goals will not be realized, if not the totality of Islamic Banking in improving service quality to customers as a form of good governance. Service quality in Islamic banking can be seen from the customer satisfaction in enjoying the quality of service desired by the customer and in accordance with the concept of Islam which require glorifying customers. Implement of customer satisfaction is the duty and obedience Islamic Banking regulated in Act No. 21 of 2008 on Islamic Banking.